Essays on economic linkages and resilience - Wiedemann, V (2023)
This thesis consists of five chapters that explore the theme of economic linkages and resilience. My research investigates the structure of Kenya's formal firm network and its connections to both international markets and the domestic informal sector. Chapter 1 discusses how tax returns can be used to map Kenya's domestic firm network and describes the network’s fundamental properties. In Chapter 2, my co-authors and I address the informal sector's significance in shaping spatial patterns of firm-to-firm trade observed in formal sector data. We document stylized facts about trade among formal firms, revealing a high degree of spatial concentration, beyond the concentration of aggregate economic activity. Using census data and a network formation model we show that solely relying on formal sector network data might underestimate both the connectivity but also vulnerability of smaller regional markets to shocks, especially those passing through hubs like Nairobi. Chapter 3 draws on qualitative interviews to study the role of Internet infrastructure in shaping supply chains. I find that a firm’s choice to adopt Internet-based technologies is influenced by its capacity to make complementary investments, which in turn correlate with to firm size. Turning to linkages of Kenya's supply chains with international markets in Chapter 4, my co-authors and I show that firms with strong direct or indirect connections to international markets tend to be older, larger, and account for a substantial share of Kenya's formal economy. We find that both importers and exporters adjust their domestic supply chains in response to international trade shocks -- before and during the COVID-19 crisis alike. Sourcing from international markets does not crowd out domestic purchases, while sales abroad and at home can act as substitutes. In Chapter 5, my co-authors and I study the impact of changes in mobility patterns during COVID-19 pandemic on food price dynamics in Kenya and Uganda. Using geo-referenced price data collected through a crowdsourcing approach, we find that a 10 percentage point reduction in mobility leads to a 0.3% and 1.5% increase in food prices in Kenya and Uganda, respectively.